Smokers' and e-cigarette users' perceptions of modified risk warnings for e-cigarettes - Olivia A. Wackowski; Richard J. O'Connor; Andrew A. Strasser; David Hammond; Andrea C. Villanti; Cristine D. Delnevo (Preventive Medicine Reports, 2016)
The 2009 Family Smoking Prevention and Tobacco Control Act opened the possibility for tobacco companies to apply to market their products as having “modified” or reduced risks. However, research on how to communicate comparative tobacco risks and how such messages are interpreted is limited. This study aimed to qualitatively examine perceptions of potential modified risk statements presented as warning labels for e-cigarettes. We conducted six focus groups between 2014 and 2015 with 27 adult e-cigarette users and cigarette-only smokers who provided comments on two versions of a modified risk warning for e-cigarettes: 1) “WARNING: No tobacco product is safe, but this product presents substantially lower risks to health than cigarettes” (as proposed by two companies for their smokeless tobacco products) and 2) “WARNING: This product may be harmful to health, but is substantially less harmful than cigarettes” (an alternative developed by our team). Although most personally believed that e-cigarettes are safer than cigarettes and some thought the messages were true and accurate, many were skeptical and uncomfortable with the warnings because they did not “seem like a warning” and because use of the phrase “substantially lower risks” could be misleading and difficult to understand. Several thought the second warning was stronger (e.g., more active, more specific). Modified risk messages about e-cigarettes may impact perceptions and use of the product. More research is needed to identify the framing, wording and placement (e.g. within or in addition to a warning) that could potentially increase population-level benefits and minimize harms. Keywords: E-cigarettes, Warning labels, Communication, Harm reduction, Modified risk, Tobacco